2010
DOI: 10.1177/1756285609356135
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations on the use of rituximab in autoimmune neurological disorders

Abstract: Rituximab (Mabthera, Rituxan) is a chimeric human/murine monoclonal antibody against CD-20 surface antigen expressed on B-cells. Rituximab, by causing B-cell depletion, appears to be effective in several autoimmune disorders; it has been approved for rheumatoid arthritis and is a promising new agent in the treatment of several autoimmune neurological disorders. A controlled study in patients with relapsing remitting multiple sclerosis has shown that rituximab significantly reduces the number of new MRI lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 89 publications
1
46
0
Order By: Relevance
“…Another study also showed rituximab resulted in effective clinical response in 79% Systemic lupus erythematosus (SLE) patients (Tokunaga et al, 2007). Kosmidis and Dalakas (2010) have summarized the effect of rituximab on some autoimmune neurological disorders improvement. They also concluded rituximab has positive effect on the treatment of autoimmune diseases.…”
Section: Resultsmentioning
confidence: 96%
“…Another study also showed rituximab resulted in effective clinical response in 79% Systemic lupus erythematosus (SLE) patients (Tokunaga et al, 2007). Kosmidis and Dalakas (2010) have summarized the effect of rituximab on some autoimmune neurological disorders improvement. They also concluded rituximab has positive effect on the treatment of autoimmune diseases.…”
Section: Resultsmentioning
confidence: 96%
“…Given the presumed direct pathogenic role of NMDA-R-Abs in this disease, as suggested by experimental studies, and the characteristic perivascular clusters of B lymphocytes in the brains of patients with NMDA-R-Abs encephalitis, some authors have suggested that rituximab could be a useful treatment, with a better outcome when administered early in the disease [8,[11][12][13][14][15]. Rituximab depletes B cells from the circulation and from [16,17]. It has been used with increasing frequency in both systemic autoimmune diseases and neurological ones, such as myasthenia gravis, neuromyelitis optica, stiff man syndrome or opsoclonus-myoclonus syndrome in both adults and children [11,[18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 97%
“…Treatment with rituximab thus selectively depletes B-lymphocytes, but not plasma cells [380]. The depletion of B-cells occurs through a combination of antibody dependent cell-mediated toxicity and complement-mediated cytotoxicity, and lasts for approximately 6 months [381].…”
Section: Rituximabmentioning
confidence: 99%